Temporary occipito-cervical stabilization of a unilateral occipital condyle fracture - Schnake, Klaus John (Springer-Verlag, 2012)
[Image: see text] INTRODUCTION: Injuries of the occipital condyles are rare. While the majority of occipital condyle fractures can be treated conservatively, surgery is recommended in craniocervical misalignment and instability. Open reduction and temporary occipito-cervical stabilization might be an alternative to fusion or halo treatment. MATERIALS AND METHODS: This Grand Round case presentation describes temporary C0–C3 stabilization in a 29-year-old man who was involved in a car accident. Radiological examination revealed a rotational burst fracture (type AO C3.1) of C7, and a slight displaced right occipital condyle fracture (Anderson/Montesano type III) with rotational misalignment of the C0–C2 complex. RESULTS: The C7 fracture was stabilized and fused from anterior and posterior. The occipital condyle fracture was reduced and temporarily stabilized from C0–C3 from posterior. Bony healing occurred after 6 months and consequently the internal fixator was removed to preserve upper cervical mobility.